Video for Fig. 4b - Wang, Chong; Sun, Yongle; Chen, Guangyu; Chen, Xin; Ding, Jialuo; Suder, Wojciech; Diao, Chenglei; Williams, Stewart (Cranfield University, 2022)
This is a supplementary video for Fig 4b, showing the hybrid PTA-laser melting process with a laser leading configuration.
Keywords: 'Hybrid plasma arc-laser additive manufacturing'; 'Steady-state finite element model'; 'Orthotropic artificial conductivity'